Sosialisasi Penggunaaan Kantong Tatakura untuk Mengurangi Masalah Limbah Padat Rumah Tangga - Kamaliah Kamaliah; Nani Apriyani; Sari Marlina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Household solid waste produced by households can be processed into compost by using takakura sacs. The purpose of this activity is to give information to the community in Kelurahan Kalampangan about the using of Takakura sacs in making compost from household solid waste. The implementation of this activity carried out by delivery information and demonstration methods. The activity was held on Wednesday, January 20, 2016, from 13:30 to 17:00 pm. The event began with the opening, the delivery of materials using the media leaflet followed by questions and answers. The material presented was a way of making a starter to facilitate the decay of household solid waste and the using of Takakura sacs to make compost. This activity was successfully implemented because of the positive response and enthusiasm from the women of farmer group in Kelurahan Kalampangan.